PERIVENTRICULAR HYDATID CYST PRESENTING WITH HEMICHOREA - (:unkn) unknown (SPRINGER VERLAG, 1992)
A case of periventricular hydatid cyst presenting with only hemichorea is reported. The unusual clinical course is described.
Keywords: COMPUTED TOMOGRAPHY; HEMICHOREA; HYDATID CYST